Comparison Of Variations Of Low Dosage Spinal Anesthesia On Mobilization Speed After Caesarea Sectio Eracs Method At Hermina General Hospital Purwokerto - Syahira, Zazza; Riyanto, Refni; Susiyadi, Susiyadi; Maududi, Muhammad Saifulhaq (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2024)
Enhanced Recovery After Caesarian Surgery (ERACS) is the development of sectio caesarean delivery techniques that offer preoperative, intraoperative, and postoperative care to hasten patient recovery. The ERACS technique is related to using low-dose spinal anesthesia, which is using a bupivacaine dose of 3.75–12 mg. The use of low doses in sectio caesarean can help the speed of patient mobilization, which can be measured by achieving a Bromage score. The study aims to compare the effectiveness of giving low-dose spinal anesthesia type bupivacaine 6 mg compared to bupivacaine 7.5 mg on the post-sectio caesarea mobilization speed of the ERACS (Enhanced Recovery After Caesarian Surgery) method at Hermina General Hospital Purwokerto. This type of research is observational and analytical with a cross-sectional study approach. The sampling technique used was consecutive sampling, so a study sample of 58 respondents was obtained, which was divided into two groups, namely the bupivacaine dose group of 6 mg and the bupivacaine dose group of 7.5 mg. Results were analyzed using the Mann-Whitney test. The results of statistical tests showed that the bupivacaine group at a dose of 6 mg and the bupivacaine group at a dose of 7.5 mg (p = 0.534) did not have a significant difference in effectiveness against the onset of post-sectio caesarean mobilization speed of the ERACS method (P > 0.05). This study concludes that there is no difference between the comparison of the effectiveness of administering low-dose spinal anesthesia type bupivacaine 6 mg compared to bupivacaine 7.5 mg on the speed of mobilization after caesarean section using the ERACS (Enhanced Recovery After Caesarian Surgery) method at Hermina General Hospital Purwokerto. The maximum time achieved for the onset of mobilization after ERACS to achieve a bromage score is in the range of 1 – 2 hours (60 – 120 minutes) with the level of mobilization after caesarean section being a score of 1 and a score of 0.